Development of 'Core Outcome Sets' for meningioma in clinical studies: The COSMIC project. (15th October 2021) - Millward, Christopher; Keshwara, Sumirat; Islim, Abdurrahman; Srikandarajah, Nisaharan; Marson, Tony; Williamson, Paula; Jenkinson, Michael
Abstract: Aims: To date, meningioma clinical trial activity has been limited, but a number of high-quality studies are underway, with more in development. There is heterogeneity in the outcomes reported in meningioma clinical trials. The COSMIC Project will develop two 'Core Outcome Sets' (COS) through comprehensive, transparent, consensus methodology; to ensure outcomes relevant to key stakeholders are reported within and across future meningioma clinical studies. The first will be for use in clinical effectiveness trials (COSMIC: Intervention), the second will be for use in clinical studies of incidental meningioma (COSMIC: Observation). Method: Three systematic literature reviews will be performed to generate a long-list of outcomes potentially relevant to meningioma patients, healthcare professionals, researchers, and other stakeholder groups. The first systematic review will present the outcomes reported in published and ongoing meningioma clinical effectiveness trials. The second systematic review will present patient-reported outcomes (PRO) from the measurement tools utilised in meningioma PRO studies. The third systematic review will present the outcomes reported in published and ongoing clinical studies of untreated meningioma. Outcomes will be deduplicated, unique outcomes categorised according to the taxonomy presented by COMET, and the lists combined. The long-list of outcomes will be prioritised through two, 2-round, modified eDelphi surveys including meningioma patients, healthcare professionals, researchers, and other stakeholder groups. Undecided outcomes from both eDelphi surveys will be ratified at two, one-day consensus meeting, with representation from all key stakeholder groups. Results: We have formed a study advisory group with international representation from key organisations. The project already has confirmed support from the International Consortium on Meningioma (ICOM), the European Association of Neuro-Oncology (EANO), the Response Assessment in Neuro-Oncology Patient-Reported Outcome group (RANO-PRO), the Society for Neuro-Oncology (SNO), British Neuro-Oncology Society (BNOS), Society of British Neurological Surgeons (SBNS), The Brain Tumour Charity (TBTC), and Brainstrust. Conclusion: Standardising minimum outcome reporting in meningioma clinical effectiveness trials and meningioma clinical studies, through the development of these two COS will ensure outcomes reported are relevant to key stakeholder groups, including patients, whilst reducing research waste for a disease with increasing clinical trial activity. We seek to raise awareness of this project and invite participation from a wide range of stakeholders to ensure that the final COS reflects the opinion of the neuro-oncology community. Registration will take place via the study website www.thecosmicproject.org between June-August 2021.